Citizen science and integrative taxonomy reveal a great diversity within Caribbean Chaetopteridae (Annelida), with the description of one new species - Martin, Daniel; Mecca, Marika; Meca, Miguel A.; van Moorsel, Godfried; Romano, Chiara (Invertebrate Systematics, 2022)
Chaetopteridae forms a monophyletic clade showing an uncertain position within Annelida. The family has 75 ubiquitous species within four genera that cluster in two well-supported clades (Chaetopterus–Mesochaetopterus and Spiochaetopterus–Phyllochaetopterus) and includes several cryptic species complexes. Based on integrative taxonomy and supported by citizen science, here we describe one new and two unnamed species of Caribbean chaetopterids. Partial sequences from the nuclear 18S rRNA and mitochondrial Cytochrome Oxidase I genes of all known chaetopterid genera allowed us to (1) discuss the phylogeny of the family and (2) assign the three species into Mesochaetopterus (two) and Phyllochaetopterus (one). Mesochaetopterus stinapa, sp. nov. clearly diverged from all species of the genus, whereas Mesochaetopterus aff. xerecus forms a separate clade with Mesochaetopterus rogeri (Europe) and Mesochaetopterus xerecus (Brazil). Phyllochaetopterus aff. verrilli forms a separate clade with Phyllochaetopterus arabicus (Red Sea) and the closely related sequences from Hawai’i, Australia and French Polynesia attributed to Phyllochaetopterus verrilli (or cf. verrilli). Despite observing differences in morphology (e.g. palp colour pattern, presence or absence of eyespots, chaetal morphology and arrangement) and biogeographical distributions, only the erection of M. stinapa as a new species is well supported by the genetic distance, barcoding gap and species discrimination analyses. Our results emphasise the existence of cryptic species complexes within Mesochaetopterus and Phyllochaetopterus, whose taxonomy will require further morphological, biogeographical and molecular data to be resolved.
World Polychaeta Database (WPolyD).